Descriptions of six known species of Plectus Bastian, 1865 (Nematoda, Plectida, Plectidae) from India with a discussion on the taxonomy of the genus - Tahseen, Qudsia; Mustaqim, Malka (Zootaxa, 2012)
Detailed descriptions of six species of Plectus reported for the first time from India are given on the basis of LM and SEMobservations. Plectus geophilus de Man, 1880, P. aquatilis Andrássy, 1985, P. parvus Bastian, 1865, P. minimus Cobb,1893, P. magadani Kuzmin, 1979 and P. communis Bütschli, 1873 are described and illustrated. The salient morphologicalcharacters of the species are given. The taxonomy of the genus has been discussed along with the status of species pre-senting a great degree of morphometric overlap and continuous variation. An emended diagnosis of the genus is provided with incorporation of relatively consistent and less variable characters.